2019 IEEE EMBS International Conference on Biomedical &Amp; Health Informatics (BHI) 2019
DOI: 10.1109/bhi.2019.8834603
|View full text |Cite
|
Sign up to set email alerts
|

Computational Astrocyence: Astrocytes encode inhibitory activity into the frequency and spatial extent of their calcium elevations

Abstract: Deciphering the complex interactions between neurotransmission and astrocytic Ca 2+ elevations is a target promising a comprehensive understanding of brain function. While the astrocytic response to excitatory synaptic activity has been extensively studied, how inhibitory activity results to intracellular Ca 2+ waves remains elusive. In this study, we developed a compartmental astrocytic model that exhibits distinct levels of responsiveness to inhibitory activity. Our model suggested that the astrocytic covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Moreover, small changes in Ca 2+ buffering may influence the spread of regenerative glial Ca 2+ waves, being consistent with the slow Ca 2+ transients experimentally reported [72]. In agreement, some models of astrocyte behavior have shown that astroglial Ca 2+ waves may induce neuronal synchronization and spatial clustering of synaptic plasticity, showing that the number of inhibitory terminals that one astrocyte ensheathes is critical for the spatial extent and temporal duration of astrocytic Ca 2+ transients [73]. However, when the number of active synapses increases into an astrocytic domain, there were simultaneous Ca 2+ elevations in multiple microdomains that together were able to trigger the Ca 2+ elevations in the thicker astrocytic branches, which were spatially expanded and prolonged in time having a lower frequency [73].…”
Section: Lfp and Ca 2+ Transients In Astrocytessupporting
confidence: 86%
“…Moreover, small changes in Ca 2+ buffering may influence the spread of regenerative glial Ca 2+ waves, being consistent with the slow Ca 2+ transients experimentally reported [72]. In agreement, some models of astrocyte behavior have shown that astroglial Ca 2+ waves may induce neuronal synchronization and spatial clustering of synaptic plasticity, showing that the number of inhibitory terminals that one astrocyte ensheathes is critical for the spatial extent and temporal duration of astrocytic Ca 2+ transients [73]. However, when the number of active synapses increases into an astrocytic domain, there were simultaneous Ca 2+ elevations in multiple microdomains that together were able to trigger the Ca 2+ elevations in the thicker astrocytic branches, which were spatially expanded and prolonged in time having a lower frequency [73].…”
Section: Lfp and Ca 2+ Transients In Astrocytessupporting
confidence: 86%